1995
DOI: 10.1249/00005768-199505000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Sport and Exercise

Abstract: about courses, work-based learning and qualifications. Physiology of Sport and Exercise with Web Study. 5thth Edition You'll study biological sciences such as cell biology, genetics and molecular biology alongside sport and exercise physiology, nutrition, and sport and exercise. ?Physiology of Sport and Exercise 5th Edition: Chapter 1 Flashcards. Study Flashcards On Physiology of Sport and Exercise 5th Edition: Chapter 1 at Cram.com. Quickly memorize the terms, phrases and much more. Cram.com Physiology of Spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
777
8
122

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 818 publications
(940 citation statements)
references
References 0 publications
33
777
8
122
Order By: Relevance
“…Our finding was neither associated with onset of puberty nor disciplines closely to trauma or injuries. Sex hormones may play a central role in the aetiology of this malignancy (39) and physical activity is suggested to influence cancer development through hormonal mechanisms (40). As strenuous exercise might influence both basal and acute androgen levels (41) and also have immunosuppressive effects (3,42), these factors might explain the present observation.…”
Section: Discussionmentioning
confidence: 67%
“…Our finding was neither associated with onset of puberty nor disciplines closely to trauma or injuries. Sex hormones may play a central role in the aetiology of this malignancy (39) and physical activity is suggested to influence cancer development through hormonal mechanisms (40). As strenuous exercise might influence both basal and acute androgen levels (41) and also have immunosuppressive effects (3,42), these factors might explain the present observation.…”
Section: Discussionmentioning
confidence: 67%
“…16 Several studies reported a gender-related development of relative body weight and fat distribution in children of this age. Wilmore and Costill 17 found an impressive increase in subcutaneous fat tissues in nonobese girls at the onset of their sexual maturation, whereas boys showed no changes in the percentage of their body fat over time. However, van Lenthe et al 18 found no differences in fat distribution between nonobese males and females between the ages 13 and 27 y.…”
Section: Discussionmentioning
confidence: 97%
“…The subjects remained seated for 20 min, with their arms relaxed at the sides of the body, in a noiseless environment and with the temperature between 24 and 26°C (Wilmore et al 2010). BP was measured during the last minute of resting (MAPA, MEDITECH, Brasilia, Brazil).…”
Section: Blood Pressurementioning
confidence: 99%
“…The aging process involves a series of changes, including the reduction of the physical fitness (Wilmore et al 2010;Janssen et al 1985;Holland et al 2002), mainly of aerobic endurance, strength, and balance. These changes impact the everyday life of older adults, limiting their capacity to accomplish normal activities in a comfortable manner and increasing the risk of falls, which affects their functional independence and quality of life (Power and Howley 2000).…”
Section: Introductionmentioning
confidence: 99%